Sams teach yourself Internet and Web basics all in one - Snell, Ned (Sams teach yourself all in one., 2003)
Internet and Web Basics All in One is designed to teach the new computer user how to easily work with a variety of digital media. It doesn't assume the reader wants to learn how to use just one product, but covers multiple products and technologies together in a logical fashion: Internet Basics, Web Browsing, Email and Chat, Fun and Games, Viruses and Hackers, Creating Web Pages.